One-pot synthesis of rod-shaped gadolinia doped zinc oxide decorated on graphene oxide composite as an efficient electrode material for isoprenaline sensor. (15th April 2021) - Manjula, Natesan; Chen, Shen-Ming
Abstract: To develop the isoprenaline (ISN) sensor with a simple and convenient synthesis process, the novel gadolinia doped zinc oxide is decorated on graphene oxide (GZO@GO) nanocomposite. The GZO@GO was synthesized through a cost-effective coprecipitation approach. XRD, FT-IR, and XPS, FE-SEM, and HR-TEM studies were used to investigate the physicochemical properties of as-prepared nanomaterials. The synthesized GZO@GO composite was successfully modified with a glassy carbon electrode (GCE) and employed as a superior electrocatalyst and challenging sensing platform for ISN detection. Electron transferability of these supported catalysts is probed by electrochemical techniques i.e. CV and EIS using K3 [Fe(CN)6 ]/K4 [Fe(CN)6 ] as a redox probe. The electrochemical oxidation of ISN based on GZO@GO was monitored by CV and DPV by optimal conditions. The present sensor showed a dynamic linearity is 0.02 μM–122.1 μM; regression equation; Ipa (μM) = 8.1847 (c/μM)–0.4502 (R 2 = 0.995) with the detection limit is achieved 0.003 μM. Also, the modified electrode demonstrates good long-term reliability, reproducibility, and good anti-interference ability. The GZO@GO modified electrode displayed higher electrocatalytic activity towards ISN oxidation due to the increasing adsorption of ISN on GZO@GO modified electrode surfaces. Finally, our proposed material was applied for the ISN determination in a human urine sample with satisfactory recovery results. This work provides insights into the eco-friendly synthesis of nanocatalyst (GZO@GO) for the ISN sensor. Graphical abstract: Image 1 Highlights: A highly-active catalyst of rod shaped gadolinia doped zinc oxide decorated on GO sheet (GZO@GO) were synthesized through a simple and low-cost coprecipitation method. GZO@GO/GCE showed a superior electrochemical behavior toward ISN detection, wide range 0.02–122.1 μM with detection limit of 0.003 μM. GZO@GO/GCE is suitable for real sample analysis in urine sample.